Strategi Pemerintah dalam Menanggulangi Penyebaran Penyakit Demam Berdarah Dengue di Kota Bandung - Nur, Faiza Rahma; Karniawati, Nia (Indonesian Journal Publisher, 2024)
The spread of dengue hemorrhagic fever (DHF) continues to be a significant health problem in the city of Bandung. This research aims to evaluate the effectiveness of the government's strategy in dealing with the spread of dengue fever in the city. The type of research used is a literature study. The literature study method involves a series of activities related to collecting bibliographic data, reading and taking notes, as well as managing research materials. This research method includes secondary data analysis from government reports, field surveys, and interviews with relevant health workers. The research results show that the Bandung City government has implemented various strategies, such as a campaign to eradicate mosquito nests, provide outreach to the community, and monitor dengue cases. However, the success rate of these strategies varies. The main challenges faced include a lack of community participation, limited resources, and a lack of inter-agency coordination. In-depth evaluation is needed to evaluate the impact of strategies that have been implemented and expansion and improvement of strategies to increase their effectiveness. This research makes an important contribution to understanding the government's efforts to tackle dengue fever in the city of Bandung and highlights the importance of cross-sectoral collaboration in dealing with complex public health problems.